Modeling the Impact of Childhood Trauma on Academic Procrastination with Identity Crisis Mediation in Female High School Students - Moradi Dolatabadi, Mozhgan; Sobhi, Afsaneh; Ahmadi, Mohammad Saeid (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Academic procrastination is a common issue among students that significantly impacts their educational outcomes. The objective of this study was to explore the impact of childhood trauma on academic procrastination and examine the mediating role of identity crisis among female high school students in Karaj, Iran. This research aimed to elucidate the complex interrelationships between personal trauma, identity development, and educational behaviors. Methods and Materials: The study utilized a descriptive correlational design, employing structural equation modeling to analyze the data. A total of 384 female high school students from Karaj participated in the study. Data were collected using standardized instruments, including the Childhood Trauma Questionnaire, the Identity Crisis Questionnaire, and various measures of academic procrastination related to different academic tasks. Statistical analysis was performed using SmartPLS to assess direct and indirect relationships among the variables. Findings: The results revealed significant direct effects of childhood trauma on academic procrastination (β = .201, p < .001) and identity crisis (β = .290, p < .001). Furthermore, identity crisis significantly mediated the relationship between childhood trauma and academic procrastination (indirect effect β = .091, p < .001). These findings underscore the profound influence of early adverse experiences and identity struggles on academic behaviors. Conclusion: The study concludes that childhood trauma and identity crisis are significant predictors of academic procrastination. Identity crisis mediates the impact of childhood trauma on procrastination, suggesting that interventions addressing both psychological healing and identity development could be beneficial in reducing procrastinatory behaviors among students.